PROSES HIDROGENASI MINYAK BATUBARA UNTUK PEMENUHAN TARGET MUTU PASAR - Sugeng, Dhani Avianto (Jurnal Energi dan Lingkungan (Enerlink), 2008)
A characterization of synthetic liquefied oil from coal was conducted to preparefor further treatment of its quality. One of few techniques in improving the coal oilis done through hydrotreatment process to remove its nitrogen, sulfur, oxygenand aromatics contents known as heteroatoms which make the oil stability notgood. Experiment using small-scale fixed bed reactor shows there is animprovement in the quality of recycle solvent used for coal liquefaction after firsthydrotreatment. coal slurry using first hydrotreated oil as solvent shows lowerviscosity than that of non-hydrotreated oil, and if mixed with coal from Banko, thecoal concentration could achieve as high as 50%. Nitrogen and sulfur contents inhydrotreated oil are reduced to negligible level and the storage stability isremarkably improved after hydrotreatment. The quality of fuel from secondhydrotreatment is still lower than that of petroleum productc in terms of ‘cetanenumber’, ‘smoke point’, contents of sulfur and aromatics.Kata kunci: hydrotreatment, smoke point, fixed bed reator, heteroatom,synthetic liquefied oil, recycle solvent